Personality Analysis of the Princess Character in the Story “الأميرة الحسناء” - Angelina, Hikmah Camilatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article discusses the analysis of the personality of the Princess character in the story Al-Amirah AlHasna’ using a literary psychology approach. This study aims to describe the structure and dynamics of the Princess’s personality based on Sigmund Freud’s psychoanalytic theory, which includes the id, ego, and superego, as well as the inner conflicts and anxiety experienced by the character. The research method employed is a descriptive qualitative method with text analysis techniques, focusing on dialogues, actions, and narratives related to the main character. The results of the study indicate that the Princess character exhibits id impulses reflected in her personal desires and emotions, an ego that functions to consider reality and make rational decisions, and a superego that is evident in her moral attitudes and values. The interaction among these three personality structures creates psychological dynamics that sometimes give rise to inner conflicts and anxiety throughout the storyline. Thus, the Princess character represents the complexity of human personality as explained in Freud’s psychoanalytic theory.